PENGEMBANGAN UMKM JAJANAN TRADISIONAL DESA BINTORO DEMAK MELALUI PENINGKATAN PRODUKTIVITAS - Eviatiwi Kusumaningtyas Sugiyanto; Ratna Wijayanti; Ika Fitriani (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
Implementation of this PKM focus on efforts to improve business management and the quality of production of traditional snacks in Demak Regency. Based on the analysis, partners have problems in the fields of production and marketing. The problem in the production aspect is related to the limited use of technology, the entire production process is carried out manually which causes excess and the quality of the product to be low. Limited quantity affects the unmet market demand, while low quality caused by unhygienic production processes, uneven product texture and changing taste. Problems in the marketing aspect discuss the knowledge and skills of micro entrepreneurs in planning marketing strategies (unattractive packaging). The method used is participatory training through workshops and training. The result of the PKM implementation is that traditional snacks SMEs already have technological renewal, consisting of a jenang mixer that is useful for increasing production capacity and revenue. An Increased Understanding of traditional snacks SMEs in terms of hygienic food production and product packaging.